Analysis of monoclonal antibodies specific for the gamma alpha TcR - Davis, W.C.; Brown, W.C.; Hamilton, M.J.; Wyatt, C.R.; Orden, J.A.; Khalid, A.M.; Naessens, Jan (Elsevier, 1996)
Alpha gamma T cells in ruminants can be subdivided in two or more subpopulations on the basis of the expression of surface antigen WC1, which can exist in different isoforms. In this study, 18 monoclonal antibodies (mAbs) submitted to the Third International Workshop that were predicted to react with Alpha gamma TcR molecules were analysed and expression of their antigens was investigated on the different Alpha gamma T cell subpopulations. A set of control mAbs positive for TcR1 (86D), BoCD3 (MM1A), WC1 (B7A1, BAQ4A, CACTB32A, and BAQ89A) was included for comparative studies. Previous investigations demonstrated eight of the mAbs immunoprecipitated peptides with apparent Mrs or 37 and/or 47kDa, indicating they recognized determinants on the T cell receptor, TcR1. Two color flow cytometric analyses in the present study demonstrated the mAbs formed three groups; group 1, a set of mAbs that recognize TcR1 determinants on some alpha gamma T cells: TcR1-N6 and TcR1-N7 respectively. mAbs from the latter groups define families of TcR1 molecules that express either one or both of the determinants. These antigenically distinct forms of TcR1 are expressed in equal proportion on the two Alpha gamma T cell populations that express one of the mutually exclusive isoforms of WC1, WC1-N3 and WC1-N4. The data indicate usage of the mAb-defined families of the alpha gamma TcR is primarily restricted to the WC1+ subpopulation of alpha gamma T cells. However, a small subpopulation of CD2+, WC1- alpha gamma T cells expresses a form of TcR1 positive for the determinant TcR1-N6.